Crosscurricular Competency of Critical Thinking: Its Characterization in Students of One Mexico High School - Molina-Patlán, Candelaria (2016)
This article is derived from a research study whose objective was to determine the characteristics that high school students have which are considered to be competent in the crosscurricular competence development of critical thinking. The study had a post positivist approach. It used mixed methodology in sequential exploratory mode. In the qualitative phase, data was collected by applying semi-structured interviews to six students of the first and second high school years; the results were analyzed using an inductive encoding. In the quantitative phase a self-report with Likert scale was applied to 50 high school students. The data, at this stage, were submitted to descriptive, psychometric and relations analysis. It was found that high school students, competent in developing critical thinking, feature problem-solving, issuance of judgments and disposition towards critical thinking skills. Their solidarity, the taste for sharing their knowledge and for helping those who prompted them were highlighted. We also found that the difference between men and women in this competition is minimal, but in the classroom context the capacity of women is reflected more. These findings can be taken into account in the educational practice to boost the development of critical thinking in students, and at the same time, their learning, because knowledge, attitudes and different skills come into play when strengthening critical thinking competency through practice, which is akin to the current educational approach in Mexico, to the skills-based approach.